Environmental governance: Participatory, multi-level - and effective? - Jens Newig; Oliver Fritsch (Helmholtz-Zentrum für Umweltforschung (UFZ), 2008)
Current international and European Union environmental policies increasingly promote collaborative and participatory decision-making on appropriate and multiple governance levels as a means to attain more sustainable policies and a more effective and lasting policy implementation. The entailed shifts of geographical scale of governance can be exemplified by the EU Water Framework Directive in that higher-level policies are devolved not only to the member states but to local collaborative decision-making bodies on natural as opposed to territorial scales. To date, empirical evidence and theoretical considerations have remained ambiguous about the environmental outcomes of such modes of governance. At the same time, the relationship between multi-level governance and non-state actor involvement remains a largely uncharted terrain. Accordingly, a twofold research agenda is mapped out: How does public participation work in different governance contexts? And what potential do multi-level governance environments have to foster the effectiveness of participatory governance? Drawing on scholarly literature on multi-level governance, policy implementation, public participation and complex systems, we develop five sets of hypotheses on how the number of policy levels and geographical rescaling affect citizen participation, actor interests and policy outcomes. We present empirical results based on a comparative meta-analysis of 47 case studies in environmental governance in North America and the EU, combining qualitative and quantitative methods.
Keywords: 360; Civic participation; multi-level governance; re-scaling; policy implementation; institutional fit; meta-analysis; case survey